Exploring variations in dengue symptoms: a comparative study of 2013, 2019, and 2023 in a tertiary care hospital of Bangladesh - Wahiduzzaman, Miah; Lita, Arifin Islam; Hassan, Raian Md; Siddiki, Md Adib; Yasmin, Abida; Hossain, Md Tanim; Shaon, Shakil Ahmed (BIRDEM Medical Journal, 2024)
Background: Dengue fever remains a major public health issue in Bangladesh, with repeated outbreaks. This study compares dengue symptoms in a tertiary care hospital during 2013, 2019, and 2023. The purpose of this study is to evaluate the variations in dengue symptoms among Bangladeshi dengue patients from 2013 and 2019 to 2023. Methods: This was a cross-sectional study, conducted on 100 dengue positive patients, admitted between 1st January to 7th August 2023, to the Medicine Department, Holy Family Red Crescent Medical College and Hospital, Dhaka. Demographic data, sign and symptoms and laboratory investigation reports were collected. These data were compared with a previously published study from the same institute comparing dengue symptoms between 2013 and 2019 among admitted dengue patients. The study employed a convenience sampling method for participant selection, and data analysis was carried out using SPSS version 26. Results: Analysis of 100 sero-positive dengue cases reveals a predominant occurrence in the 20 to 40 age group (51%), with the mean age of patients being 34.5 years. Among these cases, a higher prevalence is observed in males (62%) compared to females (38%). Symptomatology exhibits variations over time, with fever being consistently present. Other symptoms such as headache (90%, 23% and 12%), retroorbital pain (45%, 3% and 16%), skin rash (16%, 4% and 1%) and constipation (32%, 1% and 5%) showing fluctuations, respectively in 2013, 2019 and 2023. Notably, a significant proportion of patients in 2023 exhibit normal ultrasound findings (53%). Conclusions: In conclusion, our study provides a comprehensive analysis of Dengue infection dynamics over a decade, highlighting significant variations in clinical manifestations, laboratory findings, and abdominal ultrasound results among Bangladeshi patients. The findings suggest that Dengue remains a considerable public health concern, with fluctuations observed in symptomatology, including fever and other associated symptoms, and changes in laboratory parameters over time. BIRDEM Med J 2024; 14(3): 131-136